Association between sleep duration and dental caries in a nationally representative U.S. population - Abdullah Alawady; Asma Alharbi; Hajar Alharbi; Sarah Almesbah; Noor Alshammari; Ahmad Alkandari; Hesham Alhazmi; Hend Alqaderi (BMC, 2023)
Abstract Background Dental caries is considered one of the most prevalent chronic diseases worldwide despite all dental public health efforts. Short sleep duration has been established as a risk factor for several medical conditions. In this study, we aimed to examine the relationship between sleep duration and dental caries. Methods Data were collected from the 2017-2018 cycle of the National Health and Nutrition Examination Survey, a nationally representative health survey conducted in the United States. Participants who completed sleep questionnaires were examined by dentists using standardized clinical criteria. Analysis was limited to Individuals aged ≥ 16 years with complete clinical oral examination data and who completed the sleep questionnaire (N = 5,205). The data were weighted to provide a national estimate, and multiple potential covariates were included in the analysis to account for the complex sample design. The main outcomes of the study were untreated dental caries and dental caries experience. The main predictor variables were average sleep hours/night and a binary variable with 7 h/night as a cut off. Multiple weighted Poisson and logistic regression analyses were conducted to test the hypothesis that people with short sleep duration are more likely to exhibit dental caries. Results This study showed a statistically significant negative relationship between sleep duration and dental caries amongst all weighted adjusted analyses conducted. For a one hour increase in average sleep hours, the Adjusted Odds Ratio (AOR) of having a dental caries experience might decrease by 0.86 (AOR = 0.86, 95% CI = 0.75-0.98, P < 0.05). Individuals who reported an average sleep of ≥ 7 h were less likely to have a dental caries experience compared to individuals who reported an average sleep of < 7 h (AOR = 0.52, 95% CI = 0.33-0.82, P < 0.05). For a one hour increase in average sleep hours, the Adjusted Mean Ratio (AMR) of having a dental caries experience might decrease by 0.97 (AMR = 0.97, 95% CI = 0.96-0.99, P < 0.05), and was lower for those who reported sleeping ≥ 7 h/night than individuals who reported sleeping < 7 h/night (AMR = 0.92, 95% CI = 0.87-0.99, P < 0.05). Conclusion Findings of this cross-sectional representative study of the U.S. population revealed a statistically significant negative association between sleep duration and dental caries. In this study, individuals who slept < 7 h/night were more likely to exhibit dental caries.